Does Policy Advocacy Generate Good PR? Evidence from Labor Unions and Minimum Wages - Jeffrey Clemens; Michael R. Strain (Institute of Labor Economics (IZA), 2023)
We develop new facts relating news coverage, interest groups, and events in the legislative histories of minimum wage increases. First, we create and validate a database of news articles that includes coverage of minimum wages and organized labor. Second, we show that policy changes predict increases in news coverage that connects organized labor and minimum wages, in particular when those articles reference high-profile interest groups and research output. Third, these policy events lead coverage of organized labor to shift towards articles about minimum wages. We observe that the minimum wage's popularity with the public makes this shift qualify as "good PR," an assessment that is supported by sentiment analysis of articles about organized labor. This public relations channel can thus help rationalize why interest groups engage in policy advocacy.
Keywords: D71; D78; P16; 330; political economy; social choice; minimum wage; unionization